Labiobaetis ludmilae sp. nov., a new mayfly species from Indochina (Ephemeroptera, Baetidae) - Kluge, Nikita J.; Vishnevskaya, Maria S. (Zootaxa, 2026)
Larvae, subimagines, imagines of both sexes and eggs of a new species, Labiobaetis ludmilae sp. nov., are described from Laos and Thailand. The larva of the new species agrees with the diagnosis of the «Labiobaetis difficilis group of species» (according to Kaltenbach & Gattolliat 2019) and differs from known species of this group and all other species of Labiobaetis by having inclined denticles on abdominal terga. The mode of folding of the subimaginal gonostyli developing under the larval cuticle is of the «Acentrella-type», rather than of the «Labiobaetis-type».